GUIDELINES FOR DEVELOPING PLANT LAYOUT AND DESIGNING FOR FOOD INDUSTRY: A CASE STUDY OF CRISPY SQUID FACTORY - Kaiarb, Attaporn; Chamnina, Paphawadee; Sea-Sio, Bunchai (RMUTT Global Business and Economics Review, 2022)
This research is conducted for the purpose of the appropriate plant layout design and improves crispy squid, Squid Seasoning Powder, and Coated Peanuts process from a case study factory. This research applies the systematic layout planning, good manufacturing practice (GMP), and hazard analysis critical control point (HACCP) to design Plant layout for food industry alternatives, under the British Retail Consortium (BRC) in respect of the production risk zone were also used to the appropriate plant layout alternatives by considering the factors such as the food allergen, materials handling distance and the number of cross-traffic points. The result shared that the best suitable layout is layout No. 3. Then more improvement the layout No. 3 with Plant layout for the food industry, reduce the risk of cross-contamination food allergen from 5 points to 0 points, materials handling distance in crispy squid process from 83 m. to 52 m. Squid Seasoning Powder from 163 m. to 72 m. and Coated Peanuts process from 90 m. to 42 m. number of cross-traffic points from 28 points to 3 points.